Developing Edugames Learning Media Based on Local Culture - Henny Suharyati; Griet Helena (International Journal of Multi Discipline Science, 2018)
Technology has become the consumption of the wider community, one of which is the entertainment needs for games. Many games are on the market but the substance is not feasible for children's consumption as well as the figures shown are derived from foreign cultures with themes emerging about violence and sadism. In order to anticipate the above situation, a study was developed to produce educational games learning media based on local culture. This research  will produce educational games products that can be specially played by children aged 7 years and over. The theme will be related to the education of character development as an independent human figure, tough, hard worker and noble character. The characters are taken from the historical story that developed among the people in the area of West Java.